NGHIÊN CỨU VAI TRÒ CHỈ THỊ SINH HỌC CỦA Collembola TRONG ĐÁNH GIÁ CHẤT LƯỢNG ĐẤT Ở KHU VỰC CHẠM CHU, TUYÊN QUANG - Nguyễn, Thị Thu Anh; Đặng, Văn An; Nguyễn, Đức Anh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDY ON COLLEMBOLA BIO-INDICATOR ROLE TO ASSESS LAND USE EFFECTS ON SOIL QUALITY IN CHAM CHU, TUYEN QUANGCollembola communities are differently affected by land use practices. This study relies on the relationships between Collembola community structures and land use systems as a proxy for characterizing changes in soil quality. Thus, Collembola community structure (density, richness of Collembola morphotypes, eco-morphological groups - edaphic, hemiedaphic and epigeic) were examined in agro-forestry ecosystems to evaluate the discriminative power of the Collembola community structure. Fifteen morphotypes of Collembola were recorded in this study, 4 belonging to the edaphic eco-morphological group, 6 hemiedaphic, and 5 epigeic. The hemiedaphic and epigeic groups, in agricultural system, were more influenced by changes in land uses than the groups in natural forest system. Collembola eco-morphological groups and density were better predictors for ecosystem functioning and can be used to distinguish differences between soil uses, reducing laboratory analysis time.